Penerapan Primary Nurse Control Board dalam Meningkatkan Kinerja Keperawatan dan Patient Safety pada Pasien Postpartum di Rumah Sakit X 2026 - Shinta Novebi Setyadevi; Cicilia Ika Wulandari (Indonesian Journal of Multidisciplinary on Social and Technology, 2026)
Background: Patient safety and quality of nursing care are key indicators of hospital service performance. The implementation of the Primary Nursing model requires a supporting tool that facilitates coordination, continuity of care, and timely clinical decision-making. The Primary Nurse Control Board (PNCB) is a visual management tool designed to support nursing care management. Objective: To describe the implementation of the Primary Nurse Control Board (PNCB) in improving nursing performance and patient safety among postpartum patients in the maternity ward of Hospital X. Methods: This study employed a case study design involving two spontaneous postpartum patients admitted to the maternity ward of Hospital X in 2026. The PNCB was implemented throughout the nursing process, including assessment, prioritization of nursing problems, intervention planning and implementation, clinical monitoring, interprofessional coordination, and evaluation of nursing outcomes. Results: The implementation of PNCB improved nursing care management by providing systematic patient monitoring, structured shift-to-shift communication, and patient allocation based on dependency levels. In the first case, pain intensity decreased, breastfeeding effectiveness improved, and no signs of infection were observed. In the second case, PNCB facilitated early identification of post-episiotomy bleeding, enabling prompt medical intervention and preventing further complications. Furthermore, PNCB supported discharge planning and enhanced continuity of nursing care. Conclusion: The implementation of the Primary Nurse Control Board contributed positively to improving nursing performance by strengthening team coordination, continuity of care, appropriate workload distribution, and early detection of clinical deterioration, thereby enhancing patient safety among postpartum patients.